Micropropagação de Melaleuca alternifolia: efeitos de 6-benzylaminopurine e do comprimento de onda fornecidos por diodos emissores de luz - Gonzales Alvarado, Antony Cristhian (2023)
Melaleuca alternifolia, or tea tree, is a species used in the pharmaceutical and cosmetic industries due to its essential oils containing antibacterial, antifungal, antiviral, anti-inflammatory, and analgesic properties. In vitro cultivation of Melaleuca can contribute to the clonal production of seedlings from superior genotypes, increasing the biomass and oil productivity in this crop. However, the development of methods and studies on factors affecting the micropropagation of the species, such as plant growth regulators, and the integration of new technologies, such as the use of light-emitting diodes (LEDs), is necessary to improve the efficiency of in vitro cultivation. The objective of this study was to test different wavelengths provided by LEDs and the presence of the cytokinin N6-Benzylaminopurine (BAP) (0.0 and 0.25 mg L-1) on the in vitro multiplication and development of Melaleuca seedlings. Nodal segments were inoculated on Murashige & Skoog culture medium with half-strength macronutrients (MS ½). The test tubes containing individual nodal segments were cultured under different wavelengths provided by LEDs: White, Blue, Red, Red and White, Red and Blue, and dark conditions. Measurements of seedling development were taken, as well as chlorophyll quantification using spectrophotometry. Analysis of nutrient absorption (Ca, Mg, and P) from the culture medium was also performed in the different treatments. The statistical design was a 2 x 6 factorial, and the variables analyzed were plant height, number of shoots, number of roots, chlorophyll A, chlorophyll B, Total Chlorophyll, and nutrient absorption (Ca, Mg, and P) from the culture medium. The main results obtained showed a significant increase in the number of shoots and fresh and dry weight, reduction in shoot height, inhibition of rooting rate, significant decrease in chlorophyll content, and nutrient absorption, such as phosphorus, in in vitro plants with the presence of 0.25 mg L-1 BAP.